Non-business students’ Perceptions and Experiences of Learning Entrepreneurship: Implications for Curriculum Developers and Lecturers in Zimbabwe - Gwendoline Vusumuzi Nani (Randwick International of Education and Linguistics Science Journal, 2022)
Non-business students pursuing business-related degrees have increased in number at one selected public university in Zimbabwe. Entrepreneurship, which is commonly thought to be a subject for business discipline students, is being studied by non-business-oriented students as part of the curriculum. The purpose of this study was to learn about non-business students' perceptions and experiences while taking the Entrepreneurship course. To collect data for a case study design based on the interpretive paradigm, semi structured questionnaires were emailed to sixteen non-business Master’s students who were purposively chosen as key informants. Thematic analysis of the findings revealed that non-business students perceived entrepreneurship to be a relevant subject, particularly in these days of depressed economies where people must be job creators rather than job seekers, and where even those in employment must generate extra income. Further research revealed Entrepreneurship to be an interesting and beneficial course that imparts entrepreneurial knowledge and skills. The study concluded that entrepreneurship is a necessary course regardless of discipline and thus recommended that it be made a mandatory course across all faculties.